THE ANALYSIS OF THE MIRROR PRAYER POEM IN HÜSEYIN AKKAYA'S BOOK POEMS PASSING THROUGH THE MIRROR - Bayram, A.; Koç, A. (Dulaty University, 2023)
Hüseyin Akkaya, born in Sivas in 1955, worked as a professor at Cumhuriyet University since 2004 and retired. In addition to being an academic, his interest in poetry has never ended due to his childhood curiosity. After his first poem, Beli Gül, he wrote his poems with the theme of "mirror". “When I started writing poems centered on the mirror nine years ago, I did not expect that there would be so many of them."I think my poem, "Living in Mirrors", which I first wrote in 2012, must have been born from a fertile source because it paved the way for other mirror poems." He describes his arrival in this way. "Mirror", which has an important place as a symbol in poetry, has been used by many poets from divan literature to the present day. The "Mirror" symbol has appeared in poems both in mystical and human terms. Akkaya, on the other hand, wrote his poem called "Mirror Prayer" as a Sufi style in his book where he compiled his poems on the symbol of "mirror". Roman Ingarden and Nicolai Hartmann are two important names in the ontological analysis method, which is one of the poetry analysis methods. Ingarden stands out in dividing assets into layers, and Hartmann stands out in dividing these layers into real and irreal asset areas. Under the guidance of this information, İsmail Tunalı examined the layers of existence in his book titled Art Ontology. The poem "Mirror Prayer" mentioned in this study was analyzed ontologically according to the layers of existence in İsmail Tunalı's book titled Art Ontology.